1998
DOI: 10.1128/mcb.18.11.6281
|View full text |Cite
|
Sign up to set email alerts
|

The Immunoglobulin Heavy Chain Locus Control Region Increases Histone Acetylation along Linked c-myc Genes

Abstract: In chromosome translocations characteristic of Burkitt lymphomas (BL) and murine plasmacytomas, c-myc genes become juxtaposed to immunoglobulin heavy-chain (IgH) sequences, resulting in aberrant c-myc transcription. Translocated c-myc alleles that retain the first exon exhibit increased transcription from the normally minor c-myc promoter, P1, and increased transcriptional elongation through inherent pause sites proximal to the major c-myc promoter, P2. We recently demonstrated that a cassette derived from fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 70 publications
(85 reference statements)
3
52
0
Order By: Relevance
“…To prepare nuclear and cytoplasmic RNA, both fractions were separated as described in nuclear run-on assay (Madisen et al, 1998), and total RNA was isolated using TRIzol. For Northern transfer, membranes were blotted with 20 mg of total RNA extracted from di erent primary and immortal CEF cells then hybridized with [a-32 P]dATP-labeled chicken p53 and glyceraldehyde-3-phosphate dehydrogenase (GAPDH) cDNA fragments derived by reverse transcription polymerase chain reaction (RT ± PCR).…”
Section: Rna Isolation and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…To prepare nuclear and cytoplasmic RNA, both fractions were separated as described in nuclear run-on assay (Madisen et al, 1998), and total RNA was isolated using TRIzol. For Northern transfer, membranes were blotted with 20 mg of total RNA extracted from di erent primary and immortal CEF cells then hybridized with [a-32 P]dATP-labeled chicken p53 and glyceraldehyde-3-phosphate dehydrogenase (GAPDH) cDNA fragments derived by reverse transcription polymerase chain reaction (RT ± PCR).…”
Section: Rna Isolation and Analysismentioning
confidence: 99%
“…Nuclei isolated from primary and immortal CEF cells were used to label the de novo synthesized transcripts with [a-32 P]UTP as described previously (Madisen et al, 1998). Nuclear run-on transcription rates were determined by the Figure 7 The half-life of p53 N +LacZ 7N fusion mRNA in primary and immortal CEF cells.…”
Section: Nuclear Run-on Assaysmentioning
confidence: 99%
“…It is of interest to compare our results with MHS4 and the 9 -12), to MSH1234 with the MHS4 NF-B site mutated (columns [13][14][15][16], and with the c-myc promoter with both NF-B sites mutated linked to wild type MHS1234 (columns [17][18][19][20]. For the co-transfection studies, 2 g of c-myc promoter construct was used with 0, 1, 4, or 8 g of the super-repressor IB␣ expression vector in columns 1, 5, 9, 13, and 17; columns 2, 6, 10, 14, and 18; columns 3, 7, 11, 15, and 19; and columns 4, 8, 12, 16, and 20, respectively.…”
Section: Fig 3 Emsa and Uv Cross-link Analysis Of The Nf-b Site In mentioning
confidence: 99%
“…Recently, it has been shown that MHS1-MHS4 increase expression from the c-myc P2 promoter by an increase in histone acetylation. However, this increase in acetylation does not explain the MHS1-4 activation of transcription from the P1 promoter (16). Enhancers have been located downstream of two human C␣ genes (17)(18)(19), and these regions share some homology with the murine HS1-4, but only limited functional studies have been performed on the human enhancers.…”
mentioning
confidence: 99%
“…Enhancers increase either the rate of transcription, the number of the templates engaged in transcription, or both. Studies using transgenes or in vitro templates have linked enhancer activities to various events such as PIC assembly (Kim et al 1998;Yie et al 1999), histone acetylation at the promoter (Madisen et al 1998), and nuclear localization (Francastel et al 1999). However, it is poorly understood which events in transactivation are the actual targets of long-range enhancer function at native gene loci.…”
mentioning
confidence: 99%